2023
DOI: 10.3390/pharmaceutics15061704
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Perampanel in Portuguese Patients Diagnosed with Refractory Epilepsy

Abstract: Perampanel is a promising antiepileptic drug (AED) for refractory epilepsy treatment due to its innovative mechanism of action. This study aimed to develop a population pharmacokinetic (PopPK) model to be further used in initial dose optimization of perampanel in patients diagnosed with refractory epilepsy. A total of seventy-two plasma concentrations of perampanel obtained from forty-four patients were analyzed through a population pharmacokinetic approach by means of nonlinear mixed effects modeling (NONMEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Therapeutic drug monitoring (TDM) is an essential tool to address this complexity, enabling the definition of individual therapeutic concentrations and adaptive control of dosing to minimize drug interactions and prevent loss of efficacy or toxicity ( Krasowski, 2010 ). Some studies have shown that PER plasma levels were affected by otherAEDs in routine TDM practice, including carbamazepine, phenobarbital, valproate and topiramate ( Patsalos et al, 2016 ; Contin et al, 2018 ; Silva et al, 2023 ). A recent study indicated that enzyme-inductive AED could increase PER clearance ( Fujita et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) is an essential tool to address this complexity, enabling the definition of individual therapeutic concentrations and adaptive control of dosing to minimize drug interactions and prevent loss of efficacy or toxicity ( Krasowski, 2010 ). Some studies have shown that PER plasma levels were affected by otherAEDs in routine TDM practice, including carbamazepine, phenobarbital, valproate and topiramate ( Patsalos et al, 2016 ; Contin et al, 2018 ; Silva et al, 2023 ). A recent study indicated that enzyme-inductive AED could increase PER clearance ( Fujita et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%